(-2,8) (1,2)
m=2-8/1-(-2)
m=-6/3
m= -2
y=-2x+b
(-2,8)
8=-2(-2)+b
8=-4+b
12=b
b=12
y=-2x+12
Hope this helps!
Answer:
13
Step-by-step explanation:
g(4) will be found by putting 4 in for r.
g(4) = 25 - 3(4)
g(4)= 25 - 12
g(4) = 13
Answer:
w
Step-by-step explanation:
Answer:
6 because 6 is the x value
Step-by-step explanation:
Let the cost of each drink is $x and the cost of each hot dog is $y.
According to the given data, 3 drinks and 2 hot dogs cost $4.80. In equation form, we can write it as:
![3x+2y=4.80](https://tex.z-dn.net/?f=3x%2B2y%3D4.80)
1 drink and 1 hot dog costs $2.00. In equation form, we can write it as:
![x+y=2](https://tex.z-dn.net/?f=x%2By%3D2)
![x=2-y](https://tex.z-dn.net/?f=x%3D2-y)
Using this value of x in first equation, we get:
![3(2-y)+2y=4.80 \\ 6-3y+2y=4.80 \\ 6-y=4.80 \\ y=6-4.80 \\ y= 1.20](https://tex.z-dn.net/?f=3%282-y%29%2B2y%3D4.80%20%5C%5C%20%0A6-3y%2B2y%3D4.80%20%5C%5C%20%0A6-y%3D4.80%20%5C%5C%20%0Ay%3D6-4.80%20%5C%5C%20%0Ay%3D%201.20)
Thus the cost of one hot dog is $1.20